Neurological Injury in Intermediate‐Risk Transcatheter Aortic Valve Implantation. Issue 11 (15th November 2016) - Fanning, Jonathon P.; Wesley, Allan J.; Walters, Darren L.; Eeles, Eamonn M.; Barnett, Adrian G.; Platts, David G.; Clarke, Andrew J.; Wong, Andrew A.; Strugnell, Wendy E.; O'Sullivan, Cliona; Tronstad, Oystein; Fraser, John F.
Abstract : Background: The application of transcatheter aortic valve implantation (TAVI) to intermediate‐risk patients is a controversial issue. Of concern, neurological injury in this group remains poorly defined. Among high‐risk and inoperable patients, subclinical injury is reported on average in 75% undergoing the procedure. Although this attendant risk may be acceptable in higher‐risk patients, it may not be so in those of lower risk. Methods and Results: Forty patients undergoing TAVI with the Edwards SAPIEN‐XT ™ prosthesis were prospectively studied. Patients were of intermediate surgical risk, with a mean±standard deviation Society of Thoracic Surgeons score of 5.1±2.5% and a EuroSCORE II of 4.8±2.4%; participant age was 82±7 years. Clinically apparent injury was assessed by serial National Institutes of Health Stroke Scale assessments, Montreal Cognitive Assessments (MoCA), and with the Confusion Assessment Method. These identified 1 (2.5%) minor stroke, 1 (2.5%) episode of postoperative delirium, and 2 patients (5%) with significant postoperative cognitive dysfunction. Subclinical neurological injury was assessed using brain magnetic resonance imaging, including diffusion‐weighted imaging (DWI) sequences preprocedure and at 3±1 days postprocedure. This identified 68 new DWI lesions present in 60% of participants, with a median±interquartile range of 1±3 lesions/patient and volumes of infarction of 24±19 μL/lesion and 89±218 μL/patient. DWI lesions were associated with a statistically significant reduction in early cognition (mean ΔMoCA −3.5±1.7) without effect on cognition, quality of life, or functional capacity at 6 months. Conclusions: Objectively measured subclinical neurological injuries remain a concern in intermediate‐risk patients undergoing TAVI and are likely to manifest with early neurocognitive changes. Clinical Trial Registration: URL:http://www.anzctr.org.au . Australian & New Zealand Clinical Trials Registry: ACTRN12613000083796.